Letramentos e o ensino de história nos anos iniciais - Puckes, Edilbeth Graciella Ortt (2024)
The present research was developed around two axes encompassed the teaching of History in the early years of elementary school: the current educational curricula and multiple literacies. We carried out a dialogue with the authors: Abud (1993 e 2012), Fonseca (2003 and 2009), Kosselleck (2006), Schmidt (2012), Teodoro (2020), Ramos (2020) and others, who helped understanding of the what it is, how it is constituted and the social relevance of History teaching. The three main curricular documents analyzed were: a) National Common Curricular Base (2017); b) Document of Curricular Reference for Mato Grosso (2018); c) Educational Policy of the Municipal Education Network of Cuiabá/MT, called Escola Cuiabana: culture, life times, learning rights and inclusion (2019). The bibliographic analysis made it possible to punctuate the following concepts: Literacies (Freire, 1975 and 1996 and Soares, 1998 and 2005); Multiliteracies (Rojo, 2012); Digital Literacies (Azevedo et al, 2018; Rodrigues, 2018 and Fronza and Rodrigues Junior, 2021); Literacies and historical awareness (Rüsen, 2001 and 2010; Lee, 2006; Azevedo, 2014 and Rocha, 2020) and Historical-Digital Literacies (Silva, 2018). The documentary and bibliographical analyses, focusing on educational curricula, multiple literacies and the understanding that the teaching of History seize social importance, contributed to propose the Historiletrar and to defining important aspects how much the production of activities, which compose the final product of this dissertation, namely: a guide to activities, that relate legislation, theory and practice.